Feasibility of biology magazine sub-material of inheritance of traits as learning media - Hikma Artia; T. Titin; Andi Besse Tenriawaru (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
This study aims to determine the development and feasibility of biology magazine submaterial inheritance traits as a learning media for class IX junior high school. Engaging and effective learning media can increase students' understanding and interest in the material presented. The research method used is research and development (R&D) using the ADDIE model (analysis, design, development, implementation, and evaluation), but this study only covers the development stage. The instruments used in this study were interview sheets, instrument validation sheets, and magazine validation sheets. The biology magazine on the inheritance of traits was tested by five validators and analyzed using Aiken's V to determine content validity and the Interclass Correlation Coefficient to assess reliability. Validation was completed by completing a language, content, and construction questionnaire. The results of content validation obtained a validity of 0.89 with a valid category. Reliability results amounted to 0.82 in the good reliability category. The biology magazine on inheritance of traits is suitable for use in the learning process.